The YAP1/TAZ-TEAD transcriptional network regulates gene expression at neuromuscular junctions in skeletal muscle fibers - Gessler, Lea; Huraskin, Danyil; Jian, Yongzhi; Eiber, Nane; Hu, Zhaoyong; Prószyński, Tomasz J.; Hashemolhosseini, Said (Nucleic Acids Research, 2024)
We examined YAP1/TAZ-TEAD signaling pathway activity at neuromuscular junctions (NMJs) of skeletal muscle fibers in adult mice. Our investigations revealed that muscle-specific knockouts of Yap1 or Taz, or both, demonstrate that these transcriptional coactivators regulate synaptic gene expression, the number and morphology of NMJs, and synaptic nuclei. Yap1 or Taz single knockout mice display reduced grip strength, fragmentation of NMJs, and accumulation of synaptic nuclei. Yap1/Taz muscle-specific double knockout mice do not survive beyond birth and possess almost no NMJs, the few detectable show severely impaired morphology and are organized in widened endplate bands; and with motor nerve endings being mostly absent. Myogenic gene expression is significantly impaired in the denervated muscles of knockout mice. We found that Tead1 and Tead4 transcription rates were increased upon incubation of control primary myotubes with AGRN-conditioned medium. Reduced AGRN-dependent acetylcholine receptor clustering and synaptic gene transcription were observed in differentiated primary Tead1 and Tead4 knockout myotubes. In silico analysis of previously reported genomic occupancy sites of TEAD1/4 revealed evolutionary conserved regions of potential TEAD binding motifs in key synaptic genes, the relevance of which was functionally confirmed by reporter assays. Collectively, our data suggest a role for YAP1/TAZ-TEAD1/TEAD4 signaling, particularly through TAZ-TEAD4, in regulating synaptic gene expression and acetylcholine receptor clustering at NMJs.
CRIS-Team Scopus Importer:2024-02-16